Color polymorphism in Leptodactylus fuscus (Anura, Leptodactylidae): A defensive strategy against predators? - Kakazu, Sérgio [UNESP]; Toledo, Luís Felipe; Haddad, Célio F.B. [UNESP] (My University, 2010)
Color patterns are strongly related to defensive strategies in anurans. Some anurans present more than one morphotype. Leptodactylus fuscus, for example, present two morphotypes (with and without vertebral white line). The proportion of each pattern in nature is different, whereby there are always more individuals without stripes. Therefore, we speculated if this difference in the observed color pattern is due to unequal predation pressures (i.e. stronger over the striped morphotype), and/or if there is a genetic component related to autossomic heritage. To test the selective predation over the morphotypes, we prepared plasticine models of L. fuscus with both phenotypes and placed them in the field. We did not find evidence of predation selection and as we found significant relationships between the proportions of the phenotypes and Mendelian proportions, we suggest that the phenotypes observed in this species are genetically determined (involving dominant and recessive alleles) and may not have a defensive function.
Keywords: Character heritage; Coloration; Defensive strategy; Evolution; Predation; Anura; Leptodactylidae; Leptodactylus fuscus